STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) TECHNIQUE IN TEACHING WRITING NARRATIVE TEXT - Linta Hayatunisa (Journal of English and Education, 2014)
This study investigates the effectiveness of Student Teams Achievement Divisions (STAD) technique, proposed by Slavin (2005) and his colleagues, in teaching writing Narrative text. This study also investigates students’ responses to see the potential of the technique to be applied in the classroom. The study employs a qualitative case study research design. The data were obtained from several sources, including questionnaire, classroom observation (teaching process), and collection of samples of students’ texts in every meeting, which were then analysed using systemic functional grammar (SFG) in terms of generic structures and linguistic features of Narrative text. The findings reveal that Student Teams Achievement Divisions (STAD) technique is effective in teaching writing Narrative text. Data from classroom observation and students’ texts show the improvement in students’ writing skill in writing narrative text. The students write a good narrative text with clear generic structures and appropriate linguistic features. Moreover, the data from the questionnaires shows some responses from the students toward STAD technique. Firstly, STAD technique is found to be helpful for the students academically and socially. Secondly, the technique is also proven to motivate the students to learn more. However, to some extended some students did not want to participate in the team because the higher achiever students tended to dominate more in the discussion.  Based on the findings, it is recommended that STAD technique should be used in teaching English, especially in teaching writing Narrative text. However, in order to achieve maximum benefits of the technique, it is suggested that some aspects of the technique should be improved, for example, the teacher needs a clearer guidance to be given to the students, the team should be shuffled, and the activity should be more varied. Keywords: STAD, Writing, Narrative Text